2022
DOI: 10.1098/rsos.220578
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking neonates do not pay a survival cost in a free-ranging large mammal, the fallow deer (Dama dama)

Abstract: Recent debate has focused on whether variation in personality primarily reflects variation in resource allocation or resource acquisition of individuals. These two mechanisms predict different relationships between personality and survival. If personality mainly reflects variation in resource allocation, then bold (i.e. risk-taking) individuals are expected to live shorter lives, whereas the opposite pattern is expected with resource acquisition. Here we studied the relationship between neonate personality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
4
13
0
Order By: Relevance
“…younger) fawns, as also confirmed in the field by a clear positive relationship between the age of the fawns and difficulty capturing them. Body weight is also a good proxy for fawn quality, as shown previously in this population [48].…”
Section: Data Handling and Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…younger) fawns, as also confirmed in the field by a clear positive relationship between the age of the fawns and difficulty capturing them. Body weight is also a good proxy for fawn quality, as shown previously in this population [48].…”
Section: Data Handling and Analysissupporting
confidence: 80%
“…Previous research has also shown that prolonged nursing occurs in heavier offspring in other ungulates [62]. Combining these early-life characteristics of higher birth weight and faster growth rates [7,32,48] with our findings about bedsite characteristics (low visibility) and location (more distant from humans and their dogs compared with the other females in this population) [34], the offspring of bolder mothers are consistently awarded multiple survival advantages (to be further explored by future research) from in utero to young adult life stages. This provides evidence that begging mothers are better adapted to this environment than shyer females.…”
Section: Discussionmentioning
confidence: 99%
“…Heavier weights are associated with survival advantages in mammals [ 22 25 ], including in our own study site [ 45 ]. For example, young individuals are more likely to survive winter periods of decreased forage if they are heavier [ 46 ] and are less likely to be predated early in life [ 25 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, wildlife in these areas are often managed through systematic culls in order to maintain populations at regulated numbers [ 57 , 58 ]. If the provision of food to these wild individuals by humans is resulting in advantages for select individuals and the increased survival of their offspring [ 10 , 45 ], then there may potentially be associated population explosions that would require more regular and costly culling actions. If this is the case, then effective management of these feeding activities may prevent the need for increased culling before it even occurs.…”
Section: Discussionmentioning
confidence: 99%
“…If engagement with feeding interactions is not random, and instead is driven by behavioral type, then they may also only be occurring in a subset of the population. Recent studies have indicated that independent feeding of wildlife can impact the weight and growth rates of offspring (Griffin, Haigh, et al, 2023; Griffin, Haigh, Amin, et al, 2022) (Figure 2) and that the resultingly larger neonates have increased survival rates (Amin et al, 2022). This highlights the potential that artificial selection may be at work and we may involuntarily be manipulating wild populations.…”
Section: Current Knowledge Gapsmentioning
confidence: 99%